Focus in Searching Core–Periphery Structures - Martignoni, Dirk; Keil, Thomas; Lang, Markus (Organization Science, 2020)
Organizations are often conceptualized as systems of interdependent choices that exhibit a core–periphery structure. Research is inconclusive, however, regarding whether organizations should focus their search efforts on their core or peripheral choices. In this paper, we seek to reconcile contradictory arguments and suggest that the efficacy of a search focus depends on the time horizon, environmental change, and how the core and periphery interact. In so doing, we demonstrate that the directionality of interdependence and whether interdependencies occur mostly within the core or between the core and periphery are key determinants of the implications of focus. We discuss the implications of our findings for various streams of research, including research on structural inertia and business model innovation.